2020
DOI: 10.1074/mcp.ra120.002075
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Vascular Proteomics Highlights the Role of Peroxidases and Serine Proteases during Huanglongbing Disease Progression

Abstract: Huanglongbing (HLB) is the most devastating and widespread citrus disease. All commercial citrus varieties are susceptible to the HLB-associated bacterium, Candidatus Liberibacter asiaticus (CLas), which resides in the phloem. The phloem is part of the plant vascular system and is involved in sugar transport. To investigate the plant response to CLas, we enriched for proteins surrounding the phloem in an HLB susceptible sweet orange variety, Washington navel (Citrus sinensis (L) Osbeck). Quantitative proteomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 106 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…SPs have various functions in plant cells, including functions in the pathogen response (Tornero et al, 1997;Jordáet al, 1999). Specific citrus SPs were detected, suggesting that protease enzymatic activity is finely tuned during CaLas infection (Franco et al, 2020). The overexpression of XSP1 in finger lime suggests that there is specific mechanism underlying the defense against CaLas infection in finger lime tissues.…”
Section: Discussionmentioning
confidence: 99%
“…SPs have various functions in plant cells, including functions in the pathogen response (Tornero et al, 1997;Jordáet al, 1999). Specific citrus SPs were detected, suggesting that protease enzymatic activity is finely tuned during CaLas infection (Franco et al, 2020). The overexpression of XSP1 in finger lime suggests that there is specific mechanism underlying the defense against CaLas infection in finger lime tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Exudates of phloem-enriched bark tissues were extracted from stems following the procedure described elsewhere 74 . Stems were collected from small branches of spring spouts with mildly symptomatic leaves.…”
Section: Methodsmentioning
confidence: 99%
“…The markedly elevated activities of all three antioxidant enzymes were observed by Pitino et al [ 39 ]. Franco et al [ 41 ] found that in sweet orange Harmlin and N-33, Huanglongbing induced the accumulation of peroxidase transcripts, but POD enzyme activities exhibited different alterations: the enzyme activity was downregulated after infection in Harmlin, while the enzyme activity was upregulated after infection in N-33 [ 41 ]. In the tolerant cultivar Kaffir lime, Cu/Zn-SOD and POD4 were upregulated, while they were downregulated in C. sinensis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%